Different types of teaching techniques used by teachers in ESL speaking classroom: focus on secondary level Bangla medium students of Bangladesh - Haque, Rabiya (BRAC Univeristy, 2018)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2016.